KEMAMPUAN ELEKTRODA ALUMINIUM DAN TEMBAGA DALAM MENURUNKAN POLUTAN PADA LIMBAH CAIR BATIK - Fathul Jamal Al Izzudin; Zahro Manudin Hamzah; Syahdana Auni Maulidya; Puja Windu Rahayu; Rizky Amalia Rahmaputri; Dodi Satriawan (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
This study aims to determine the ability of aluminum (Al) and copper (Cu) electrodes in the electrocoagulation process to reduce organic pollutants found in batik liquid waste. This electrocoagulation process uses a plate measuring 10cm x 5cm x 0.3cm. This electrocoagulation process uses a current of 20 A and a voltage of 10 volts, 20 volts and 30 volts. The electrocoagulation process lasts for 30 minutes, where every 10 minutes an analysis is carried out to determine the ability of aluminum (Al) and copper (Cu) electrodes to reduce the levels of organic compounds in batik liquid waste. It was found that the higher the voltage and time of the electrocoagulation process using aluminum (Al) and copper (Cu) electrodes, the higher the acidity (pH), and the lower the levels of TDS, TSS, and COD in batik liquid waste. The optimum voltage and time to reduce pollutant levels in batik liquid waste is at a voltage of 30 Volts and a time of 30 minutes which is able to reduce TDS levels by 1977 ppm, TSS 60.75 ppm, COD 623.31 ppm and pH 10.94.